PENGARUH DISIPLIN DAN LINGKUNGAN SEKOLAH TERHADAP HASIL BELAJAR SISWA MA MA’ARIF 07 SUNAN DRAJAD PACIRAN LAMONGAN - Ana Mufarihatul Ula; Hadi Sunaryo; M. Khoirul ABS (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
ABSTRACTThis study aims to determine the effect of discipline and school environment on student learning outcomes. The sample in this study is MA. Ma’arif 07 sunan drajad paciran lamongan. Data collection is done by distributing questionnaires. Data analysis used in this study uses validity, reliability, normality, multiple regression analysis, and t test. The results of the study show that the learning discipline has a significant effect on student learning outcomes, and the school environment has a significant effect on student learning outcomes.Keywords: discipline, school environment, and student learning outcomes